Molecular and morphological characterization of Pyricularia and allied genera - Bussaban B. (2014)
The phylogenetic relationships of Pyricularia species and species from related genera were established from sequences of the internal transcribed spacer ribosomal RNA gene. Phylogenetic analysis disclosed a consistent correlation with spore morphology. Most Pyricularia species studied, and two species of Dactylaria that have obpyriform conidia, fell within the Magnaporthaceae cluster with high bootstrap support. Pyricularia variabilis was more related to Dactylaria, Tumularia or Ochroconis species than to the Magnaporthaceae. Dactylaria and species of Nakataea, Ochroconis, Pyriculariopsis and Tumularia were distinct from the Magnaporthaceae, and the genus Dactylaria is polyphyletic. The combination of morphological and molecular characters, such as spore morphology and ITS ribosomal DNA sequences data, suggested that conidial shape could be a primary character to distinguish Pyricularia from related genera. © 2005 by The Mycological Society of America.